Onset time and prognostic value of acute kidney injury in patients with acute myocardial infarction. (August 2021) - Kosaki, Ryota; Wakabayashi, Kohei; Sato, Shunya; Tanaka, Hideaki; Ogura, Kunihiro; Oishi, Yosuke; Arai, Ken; Nomura, Kosuke; Sakai, Koshiro; Sekimoto, Teruo; Nishikura, Tenjin; Tsujita, Hiroaki; et al.
Highlights: Even small declines in renal function are associated with worse short-term outcomes after AMI. The clinical impact of the timing of acute kidney injury (AKI) onset after AMI is unknown. Early-phase AKI is associated with poor long-term mortality. Late-phase AKI is not associated with poor long-term mortality. Careful clinical attention and intensive care should be used in patients with early-phase AKI after AMI. Abstract: Background: The mechanisms and clinical impact of acute kidney injury (AKI) after acute myocardial infarction (AMI) may differ depending on whether AKI develops during the early or late phase after AMI. The present study assessed the timing of AKI onset and the prognostic impact on long-term outcomes in patients hospitalized with AMI. Methods: The present study enrolled consecutive AMI survivors who had undergone successful percutaneous coronary interventions at admission. AKI was defined as an increase in the serum creatinine level of ≥0.3 mg/dL above the admission value within 7 days of hospitalization. AKI patients were further divided into two subgroups (early-phase AKI: within 3 days vs. late-phase AKI: 4 to 7 days after AMI onset). The primary endpoint was all-cause death. Results: In total, 506 patients were included in this study, with 385 men and a mean age of 69.5 ± 13.5 years old. The mean follow-up duration was 1289.5 ± 902.8 days. AKI developed in 127 patients (25.1%). Long-term mortality was significantly higher in the AKI group than in the non-AKI group (log-rank p < 0.001). Early-phase AKI developed in 98 patients (19.3%), and late-phase AKI developed in 28 patients (5.5%). In the multivariable analysis, early-phase AKI was significantly associated with all-cause mortality (HR 2.83, 95% CI [1.51–5.29], p = 0.0012), while late-phase AKI was not. Conclusion: Early-phase AKI but not late-phase AKI was associated with poor long-term mortality. Careful clinical attention and intensive care are needed when AKI is observed within 3 days of AMI onset.